ISOLATION AND CHARACTERISATION OF Pb RESISTANT BACTERIA FROM MARINE SEDIMENT AFFECTED BY INCONVENTIONAL TIN MINING AT SAMPUR BEACH, BANGKA TENGAH DISTRICT - Ina Miranti; Rahmad Lingga; Verry Andre Fabiani (Universitas Negeri Medan, 2021)
Offshore tin mining can causes heavy metal contamination, one of which is lead (Pb) metal. Lead pollution can causes environmental damage and toxic to living organisms. One of the methods to reduce lead pollution was by bioremediation techniques. Resistant bacteria were potential to be used as bioremediation agent. This research aimed to determine the lead level in Sampur coastal waters and to obtain bacteria that have resistance to lead (Pb). The research method was purposive sampling to take a sample of water and sediment. The AAS test results indicated that the Pb level in seawater is higher than sediment. A normal sea water pH can caused the Pb solubility in the water to be stable. The Pb level in seawater was passed the established quality standards, so that potentially cause toxicity for the aquatic biota. The highest Pb levels in sediment was found in vicinity of tin mining activities area. The isolation results showed that the number of bacteria ranged from 11,105 – 34,105 CFU/g. The higher Pb levels in sediment causing the number of bacteria will be lower. There were 7 isolates that resistant of Pb 100 ppm and constitute bacteria from the genus Alcaligens, Meniscus, Neisseria, Erythrobacter, and Alteromonas.